Javanese Leadership And Migrant Worker Repatriation: A Model For Transformative Crisis Response - Setyasih Harini; Sritami Santi Hatmini; Agung Yudhistira Nugroho (Journal of Political Issues)
This journal article presents an in-depth analysis of the leadership approach exhibited by Retno Marsudi as Minister of Foreign Affairs of Indonesia, during the critical process of withdrawing Indonesian migrant workers from multiple countries in the midst of a global health crisis. Marsudi's utilization of both transformational leadership and the Javanese leadership approach played a crucial role in shaping the outcomes of the withdrawal, while also offering broader lessons applicable to leadership, diplomacy, and crisis management. This article delves into Marsudi's integration of the Javanese leadership approach, The utilization of the Hasta Brata Javanese leadership approach by Retno Marsudi, during the process of withdrawing Indonesian migrant workers amid a global health crisis, offers a captivating case study in leadership and crisis management. By examining the fusion of transformational and Javanese leadership approaches, this study contributes to a deeper understanding of effective leadership in the face of complex crises. The lessons drawn have implications for diplomacy, cultural understanding, and crisis management in a broader global context.